2019
DOI: 10.1093/jas/skz096
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and localization of porcine calcium sensing receptor in different tissues of weaned piglets1

Abstract: Taste receptors including calcium sensing receptor (CaSR) are expressed in various animal tissues, and CaSR plays important roles in nutrient sensing and the physiology, growth and development of animals. However, molecular distribution of porcine CaSR (pCaSR) in different tissues, especially along the longitudinal axis of the digestive tract in weaned piglets are still unknown. In the present study, we investigated the distribution and localization of pCaSR in the different tissues including intestinal segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…The digestive system is also the most important barrier that could keep pathogens or toxins coming from the environment. Since the digestive system has the largest interface between the host and the environment (Flint et al, 2012), this makes the gut the largest organ of the immune system, accounting for 70% percent of the immune system (Zhao et al, 2019). Thus, maintaining a sound intestinal immune system is very important for gut health.…”
Section: Discussionmentioning
confidence: 99%
“…The digestive system is also the most important barrier that could keep pathogens or toxins coming from the environment. Since the digestive system has the largest interface between the host and the environment (Flint et al, 2012), this makes the gut the largest organ of the immune system, accounting for 70% percent of the immune system (Zhao et al, 2019). Thus, maintaining a sound intestinal immune system is very important for gut health.…”
Section: Discussionmentioning
confidence: 99%
“…A significant part of the candidate genes identified, such as the T-cell antigen receptor CD86 gene, involved in nutrient absorption and gut barrier function in pigs [ 48 ], ILDR2 , involved in the formation of epithelial cells barrier [ 49 ], HHLA2 , belonging to the B7 gene family can substantially regulate T-cell activity [ 50 ], GABARAPL2 involved in macroautophagy which plays essential roles during development and immunological phenomena [ 51 ], the ABCC13 gene, involved in xenobiotic defense [ 52 ], or the IFT57 gene, involved in inflammatory responses often associated with elevated cytokine concentrations [ 53 ], are expected to participate defense and immune response. However, it has been suggested that genes associated to immunity can have a pleiotropic effect [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…CaSRs have been found in key tissues involved in extracellular Ca 2+ and Mg 2+ homeostasis (e.g., parathyroid, thyroid, kidney, bone) and in other non-homeostatic tissues (e.g., brain, skin, etc. ), of different species [3,4]. In response to small changes in extracellular concentrations, the ECD of CaSR exhibits a strong positive homotropic cooperative response to Ca 2+ and Mg 2+ and heterotropic cooperativity to amino acids, metabolites, anions and pH [5].…”
Section: Introductionmentioning
confidence: 99%